Analyzing the Performance of Spatial Indices on Flash Memories using a Flash Simulator - Chaves Carniel, Anderson; da Silva, Tamires Brito; Bonicenha, Kairo Luiz dos Santos; Ciferri, Ricardo Rodrigues; Ciferri, Cristina Dutra de Aguiar (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2017)
Spatial databases improve the spatial query processing by employing spatial indices. Due to the advantages of flash memories over magnetic disks like faster reads and writes, there is a special interest in managing spatial indices in these memories. However, many flash memories employ a Flash Translation Layer that does not provide open access to many important statistics, restricting the performance analysis of spatial indices. Flash simulators are promising tools to improve the performance analysis of spatial indices. In this paper, we analyze the performance of several distinct configurations of spatial indices by using a flash simulator and a real flash-based solid state drive. As a result, we provide correlations between these results to check the accuracy of a flash simulator in the spatial indexing context. In addition, we discuss the possibility of using a flash simulator as a first step for benchmarking spatial indices. That is, we check if the results provided by a flash simulator can be used to decrease the number of configurations to be evaluated in real flash memories, reducing the required time of an empirical analysis.